(untitled) (Research, Society and Development, 2023)
Steven-Johnson Syndrome commonly occurs as an idiosyncratic reaction to systemic medications such as antibiotics, antiepileptics, and nonsteroidal anti-inflammatory drugs. It can also be triggered by non-pharmacological causes. It is a pathology with a significant impact on public health due to the high mortality rate. The clinical picture presents nonspecific symptoms, such as fever, odynophagia and itchy eyes. However, it is characterized by initial erythematous and livid macules, which involve the skin of the pre-sternal trunk and face, and may affect the palms of the hands and soles of the feet. Diagnosis of the syndrome requires collection of a complete clinical history, with special attention to drug exposure, thorough physical examination of the skin lesions, determination of the affected skin area, evaluation of mucosal involvement and complementary tests, such as skin biopsy for histopathological study. Prognosis is related to rapid identification of the causative drug and its discontinuation, not related to dose or type of drug. A case of Stevens-Johnson Syndrome is reported in a 70-year-old patient with epilepsy and Parkinson’s disease, in northern Brazil, emphasizing the clinical characteristics and the adopted treatment.